Penguatan Nilai-Nilai Pancasila melalui Pembelajaran PPKn di Sekolah Dasar: Study Literature Review - Rahayu Rahayu; Silvia Pritama Anggraeni; Bunga Aura Sefirly Roqiqoh Zauza; Nur Alika Dwi Rahayu; Nisfu Lailatul Azizah; Adelia Azzahra Putri Nadya (Prosiding Konferensi Ilmiah Dasar, 2026)
Pancasila serves as the state foundation and the nation's way of life; it must be instilled from the primary education level through Pancasila and Civic Education (PPKn) instruction. This study aims to analyze strategies for reinforcing Pancasila values through PPKn instruction in elementary schools. A literature review method was employed, analyzing four relevant articles published between 2021 and 2026. The findings indicate that reinforcing Pancasila values can be achieved through approaches such as value inculcation, modeling, facilitation, and the fostering of habits within the school environment. Pancasila values are not merely conveyed theoretically during instruction but are also embodied through activities such as prayer, religious observance, cooperation, flag ceremonies, gotong royong (mutual cooperation), deliberation, and mutual respect. Direct habituation is considered more effective in shaping students' character. However, globalization and technological advancements pose challenges to the reinforcement of Pancasila values. Therefore, contextual PPKn instruction, teacher modeling, and consistent habituation are essential to shaping students' character in alignment with Pancasila values.